Nitrate and nitrosative chemistry within Barrett's oesophagus during acid reflux. Issue 11 (13th October 2005) - Suzuki, H; Iijima, K; Scobie, G; Fyfe, V; McColl, K E L
Abstract : Background and aims: When saliva, with its high nitrite content derived from the enterosalivary recirculation of dietary nitrate, meets acidic gastric juice, the nitrite is converted to nitrous acid, nitrosative species, and nitric oxide. In healthy volunteers this potentially mutagenic chemistry is focused at the gastric cardia. We have studied the location of this luminal chemistry in Barrett's patients during acid reflux. Methods: Ten Barrett's patients were studied before and after administration of 2 mmol nitrate. Using microdialysis probes we measured nitrite, ascorbic acid, total vitamin C, and thiocyanate concentrations and pH simultaneously in the proximal oesophagus, Barrett's segment, hiatal sac, proximal stomach, and distal stomach. In a subgroup, real time nitric oxide concentrations were also measured. Results: During acid reflux, Barrett's segment was the anatomical site with maximal potential for acid catalysed nitrosation, with its median concentration of nitrite exceeding that of ascorbic acid in two of 10 subjects before nitrate and in four of nine after nitrate. Thiocyanate, which catalyses acid nitrosation, was abundant at all anatomical sites. On entering the acidic Barrett's segment, there was a substantial fall in nitrite and the lowest ascorbic acid to total vitamin C ratio, indicative of reduction of salivary nitrite to nitric oxide at this anatomical site. Episodes of acid reflux were observed to generate nitric oxide concentrations of up to 60 μM within the Barrett's segment. Conclusion: The interaction between acidic gastric refluxate and nitrite rich saliva activates potentially mutagenic luminal nitrosative chemistry within Barrett's oesophagus.